1994
DOI: 10.1128/iai.62.8.3320-3328.1994
|View full text |Cite
|
Sign up to set email alerts
|

Genes encoding high-molecular-weight adhesion proteins of nontypeable Haemophilus influenzae are part of gene clusters

Abstract: We previously reported the cloning and sequencing of genes designated hmwl and hmw2 from a prototype nontypeable Haemophilus influenzae strain. The genes encode proteins which are related to filamentous hemagglutinin ofBordeteila pertussis and promote attachment of the nontypeable H. influenzae strain to human

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 25 publications
0
54
0
1
Order By: Relevance
“…The 1B and 2B genes are 1.635 kb long and encode proteins that are 99% identical, while the 1C and 2C genes are 1.95 kb long and code for polypeptides that are 96% identical. In a recent study, we reported that, in experiments with Escherichia coli harbouring the hmw1 locus, deletion of part of hmw1C or all of hmw1C plus part of hmw1B resulted in defective processing and a loss of bacterial adherence (Barenkamp and St Geme, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The 1B and 2B genes are 1.635 kb long and encode proteins that are 99% identical, while the 1C and 2C genes are 1.95 kb long and code for polypeptides that are 96% identical. In a recent study, we reported that, in experiments with Escherichia coli harbouring the hmw1 locus, deletion of part of hmw1C or all of hmw1C plus part of hmw1B resulted in defective processing and a loss of bacterial adherence (Barenkamp and St Geme, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…S1A). The other three YtpsA proteins harbor an N-terminal extension in their SP, as also seen in FHA (Delisse-Gathoye et al, 1990), HMW1A (Barenkamp & St Geme, 1994), and LspA1 (Ward et al, 1998). Residues in this extension appear to be more conserved than those in the subsequent regions of the SP.…”
Section: Further Analyses Of the Tps Systems In Y Pestis Kimmentioning
confidence: 87%
“…Whole-cell sonicates were prepared by resuspending bacterial pellets in 10 mM HEPES, pH 7.4 and sonicating to clarity. Proteins released from the surface of the organism were recovered by precipitating culture supernatants with 10% trichloroacetic acid (TCA) as described previously (Barenkamp and St. Geme, 1994). Total membranes were recovered by centrifugation of cleared bacterial sonicates.…”
Section: Methodsmentioning
confidence: 99%
“…HMW1 and HMW2 are expressed by~80% of non-typeable H. influenzae clinical isolates and are encoded by separate chromosomal loci, each consisting of three genes, designated hmwA, hmwB and hmwC (Barenkamp and St. Geme, 1994;Buscher et al, 2004). The hmwA gene encodes the adhesin (the TpsA protein), the hmwB gene encodes the outer-membrane translocator protein (the TpsB protein), and the hmwC gene encodes a protein with possible glycosyltransferase activity (Barenkamp and St. Geme, 1994;St. Geme and Grass, 1998;Grass et al, 2003;Surana et al, 2004).…”
Section: Introductionmentioning
confidence: 99%